2022
DOI: 10.1002/bimj.202200035
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing estimation methods for integrating probability and nonprobability survey samples with machine‐learning techniques. An application to a Survey on the impact of the COVID‐19 pandemic in Spain

Abstract: Web surveys have replaced Face‐to‐Face and computer assisted telephone interviewing (CATI) as the main mode of data collection in most countries. This trend was reinforced as a consequence of COVID‐19 pandemic‐related restrictions. However, this mode still faces significant limitations in obtaining probability‐based samples of the general population. For this reason, most web surveys rely on nonprobability survey designs. Whereas probability‐based designs continue to be the gold standard in survey sampling, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[20] showed that Gradient Tree Boosting can lead to selection bias reductions in situations of high dimensionality or where the selection mechanism is Missing at Random (MAR). [25,26,27,28,29,30,31] have applied boosting algorithms in propensity score weighting showing better results than conventional parametric models.…”
Section: Weight Adjustment Based On Propensitiesmentioning
confidence: 99%
“…[20] showed that Gradient Tree Boosting can lead to selection bias reductions in situations of high dimensionality or where the selection mechanism is Missing at Random (MAR). [25,26,27,28,29,30,31] have applied boosting algorithms in propensity score weighting showing better results than conventional parametric models.…”
Section: Weight Adjustment Based On Propensitiesmentioning
confidence: 99%
“…The most commonly used method for PSA is logistic regression, but recent research showed that different machine learning methods can be advantageous in estimating the propensity score. At this point, it is not yet clear which algorithm is preferred for different distributions 18 20 .…”
Section: Related Workmentioning
confidence: 99%